Diversity Biological Food in the Yards of the Skouw Village Community Muara Tami District - Judith Lainsamputty; Alfred A. Antoh; Basa T. Rumahorbo (Postgraduate, University of Mataram, 2024)
This research aims to analyze the value of the diversity of plant types in the yards of the people of Skouw Sae village, Muara Tami District, Jayapura City. Research data collection was carried out by surveying and analyzing yard plant vegetation. Biodiversity data were analyzed using PAST (Paleontological Statistics) software version 4.09. Analysis of yard plant vegetation in the people of Skouw Sae village, Muara Tami District, Jayapura City was obtained from 20 house yards and obtained 27 plant species which were distributed at almost all stations or planted in people's houses. There are 5 strata of food plant vegetation in people's yards with varying numbers of individuals. The first stratum consisted of 895 individuals, the second stratum 32 individuals, the third stratum 122 individuals, the fourth stratum 281 individuals, and the fifth stratum 570 individuals. If we look at the number of strata species, it is found that the first stratum consists of 12 species, the second stratum is 5 species, the third stratum is 10 species, the fourth stratum is 11 species, and the fifth stratum is 9 species. Overall, the diversity of food plants found in the yards of the people of Skouw Sae village can be categorized as moderate (H'= 1.49).